Quality of Sick Child-Care Delivered by Community Health Workers in Tanzania - Colin Baynes; Dominic Mboya; Samuel Likasi; Doroth Maganga; Senga Pemba; Jitihada Baraka; Kate Ramsey; Helen Semu (Kerman University of Medical Sciences, 2018)
Background Community health worker (CHW) interventions to manage childhood illness is a strategy promoted by the global health community which involves training and supporting CHW to assess, classify and treat sick children at home, using an algorithm adapted from the Integrated Management of Childhood Illness (IMCI). To inform CHW policy, the Government of Tanzania launched a program in 2011 to determine if community case management (CCM) of malaria, pneumonia and diarrhea could be implemented by CHW in that country. Methods This paper reports the results of an observational study on the CCM service delivery quality of a trial cohort of CHW in Tanzania, called WAJA. In 2014, teams of data collectors, employees of the Ministry of Health and Social Welfare trained in IMCI, assessed the IMCI skills rendered by a sample of WAJA on sick children who presented to WAJA with illness signs and symptoms in their communities. The assessment included direct observations of WAJA IMCI episodes and expert re-assessment of the same children seen by WAJA to assess the congruence between the assessment, classification and treatment outcomes of WAJA cases and those from cases conducted by expert re-assessors. Results In the majority of cases, WAJA correctly assess sick children for CCM-treatable illnesses (malaria, pneumonia, and diarrhea) and general danger signs (90% and 89%, respectively), but too few correctly assess for physical danger signs (39%); on classification in the majority of cases (73%) WAJA correctly classified illness, though more for CCM-treatable illnesses (83%). In majority of cases (78%) WAJA treated children correctly (84% of malaria, 74% pneumonia, and 71% diarrhea cases). Errors were often associated with lapses in health systems support, mainly supervision and logistics. Conclusion CCM is a feasible strategy for CHW in Tanzania, who, in the majority of cases, implemented the approach as well as IMCI expert re-assessors. Nevertheless, for CCM to be effective, in Tanzania, a strategy to implement it must be coordinated with efforts to strengthen local health systems.